Family taxation, fertility, and horizontal equity: A political economy perspective - Alessandro Balestrino (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper intends to make a two-fold contribution to the literature. First, it studies a political economy model of family taxation using a household economics approach to behaviour; the nature of the winning policy is found to depend on whether i) the parents control their fertility or not, ii) they value their children or not. Second, it investigates the question whether the winning policy is capable to achieve horizontal equity (i.e. the requirement that all agents who are in all relevant senses identical should be treated identically); it turns out that under endogenous fertility, any winning policy trivially satisfies horizontal equity, but if fertility is exogenous for some of (or all) the parents, horizontal equity is virtually impossible to satisfy. The assessment on whether a given family taxation scheme attains horizontal equity objectives cannot therefore be independent from the assessment on the nature of fertility behaviour.
Keywords: D13; D72; H31; J13; 330; family taxation; horizontal equity; fertility; political economy; median voter; family size